Purification and characterization of protease Produced by bacillus cereus nc77 - KUSUMA DORCAS,; VASAVI DATHAR,; PAVAN KUMAR PINDI, (International Journal of Pharma and Bio Sciences, 2016)
Bacillus cereus NC77 (NCBI Accession no KX674257), a soil isolate was grown in casein agar and later shake flask method was used for protease production. The enzyme was purified by ammonium sulphate precipitation followed by dialysis and further concentrated by ion exchange chromatography. The SDS-PAGE revealed molecular weight of the protease to be 29 kDa. The specific activity of purified enzyme was found to be 2.64 U/mg and 6.13 fold purity. The enzyme yield was 75.42% from crude protein. The optimum pH ranged from 7.0 to 8.0, while the optimum temperature was 900C. The enzyme showed maximum activity with 0.9% casein as substrate. It also showed increase in activity with 0.1M Mn2+, while its activity was inhibited by 5mM of beta mercaptoethanol. 1mM of Zn2+ metal ion showed maximum protease activity. Protease enzyme of B. cereus NC77 has several advantages with an alkaline pH, thermostability and metallo enzymatic activity cooperatively which can be beneficial in industries.